Analisis Faktor yang Memengaruhi Ekspor Kunyit Indonesia dan India ke Amerika Serikat dan Inggris: Analysis of Factors Affecting Indonesian and Indian Turmeric Export to The United States and The United Kingdom - Novindra, Novindra; Nurjanah, Iga (Journal of Integrated Agribusiness, 2025)
Turmeric is a high-value bio-pharmaceutical commodity with strong production potential, diverse uses, and strategic importance as a spice export. The United States and the United Kingdom are among the largest global importers of turmeric and key target markets for Indonesia. However, Indonesia’s export share to these countries has fluctuated due to various economic factors. Meanwhile, India—despite being the world’s largest producer and exporter of turmeric—faces challenges in sustaining its export growth in these major markets. This study analyzes the factors affecting turmeric exports from Indonesia and India to the U.S. and U.K. using a panel data regression model. The findings reveal that Indonesia’s exports are significantly and elastically influenced by the average real GDP of destination countries and interest rates, with elasticity values greater than one. In contrast, the elasticity for domestic production is near one, indicating a proportional response. India shows lower elasticities for all variables, each below one. Furthermore, production is not a significant factor for either country, suggesting that increasing output alone is insufficient without downstream processing and improved market access. These results indicate that Indonesia’s turmeric exports are more responsive to external economic changes, reflecting stronger adaptability in global trade.